EPID-09. VARIATION IN GLIOMA INCIDENCE AMONG US HISPANICS BY GEOGRAPHIC REGION OF ORIGIN. (12th November 2021) - Walsh, Kyle; Bondy, Melissa; Kruchko, Carol; Huse, Jason; Amos, Christopher; Barnholtz-Sloan, Jill; Ostrom, Quinn
Abstract: BACKGROUND: Glioma incidence is 25% lower in U.S. Hispanics than in White non-Hispanics. The US Hispanic population is diverse and registry-based analyses may mask incidence differences associated with geographic/ancestral origins. METHODS: County-level glioma incidence data in U.S. Hispanics were retrieved from the Central Brain Tumor Registry of the United States (CBTRUS), which includes data from the Centers for Disease Control's National Program of Cancer Registries and the National Cancer Institute's Surveillance, Epidemiology, and End Results program and covers 100% of the U.S. population. American Community Survey (ACS) data were used to determine county-level proportion of the Hispanic population of Mexican/Central American origin, Caribbean origin (Puerto Rican, Cuban, Dominican), or other origin. Incidence rate ratios (IRRs) were generated to assess the association of glioma incidence in Hispanics with predominant origin group. RESULTS: Compared to Hispanics living in predominantly Caribbean-origin counties, Hispanics in predominantly Mexican/Central American-origin counties were at lower age-adjusted risk of glioma (IRR=0.83; P< 0.0001), glioblastoma (IRR=0.86; P< 0.0001), diffuse and anaplastic astrocytoma (IRR=0.78; P< 0.0001), oligodendroglioma (IRR=0.82; P< 0.0001), ependymoma (IRR=0.88; P=0.0121), and pilocytic astrocytoma (IRR=0.76; P< 0.0001). Associations were consistent in children and adults, and when using more granular regions of origin. However, Central American origin was associated with modestly increased incidence of several lower-grade glioma histologies. Associations were only partially attenuated after adjusting for state-level estimated of European admixture in Hispanics using 23andMe data. CONCLUSIONS: Glioma incidence in U.S. Hispanics differs significantly in association with the geographic origins of the Hispanic community, with those of Mexican/Central American origin at significantly reduced risk relative to those of Caribbean origin. U.S. Hispanics are culturally, socioeconomically, and genetically diverse. Although classified as a single ethnic group in most registry data, more granular analytic approaches could advance cancer epidemiology and disparities research.